An Algorithm for Load Balancing in Cloud Computing - Afsana,; Deswal, Suman (International Journal of Computer Sciences and Engineering, 2018)
In today’s scenario, cloud computing is considered as the most extensively spreading platform to execute tasks. These tasks are executed with the help of virtual machines as processing elements. The scheduling of tasks in a cloud computing environment is an important issue as several tasks run on cloud and users sends continuous request to the cloud. The multiple jobs running in parallel slow down the cloud system. The choice of proper scheduling algorithm decreases the cost of executing independent application on cloud resources and improves the performance. Several scheduling techniques are proposed to maintain performance of cloud environment. This paper presents a new algorithm called Suffrage algorithm for scheduling tasks in a cloud computing environment. The proposed algorithm is compared with the existing FCFS and Min-Min algorithms. The comparative analysis of FCFS, Min-Min and Suffrage shows that the Suffrage algorithm performs better than the existing algorithms in terms of makespan time, deadline and finishing time.